2019
DOI: 10.5114/aoms.2019.86976
|View full text |Cite
|
Sign up to set email alerts
|

The direct effect of lipopolysaccharide on an isolated heart is different from the effect on cardiac myocytes in vitro

Abstract: Introduction: Lipopolysaccharide (LPS) is widely used to induce experimental animals. However, its effects on cardiac contraction is controversial. Although LPS probably induces its influence in vivo both directly and indirectly, we focused on the direct effects of LPS in this report. Material and methods: Isolated ventricular myocytes mounted on a Langendorff apparatus were perfused with LPS. The changes in cultured H9c2 cells incubated with LPS over a 3-h exposure were compared with the changes after a 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The purpose of this study was to use LPS to induce a renal inflammatory cell model and then knock down ADAMTS18 to explore the mechanisms underlying its effect on inflammatory factors and renal cell activity. LPS has been intensively used as an effective tool to induce inflammation and thus explore a novel biomarker of the inflammatory response [ 17 , 18 ]. Related studies have reported that PRTECs, as early and important target cells of LPS, can be used to study various renal inflammatory responses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to use LPS to induce a renal inflammatory cell model and then knock down ADAMTS18 to explore the mechanisms underlying its effect on inflammatory factors and renal cell activity. LPS has been intensively used as an effective tool to induce inflammation and thus explore a novel biomarker of the inflammatory response [ 17 , 18 ]. Related studies have reported that PRTECs, as early and important target cells of LPS, can be used to study various renal inflammatory responses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%